2021
DOI: 10.1002/jcop.22762
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of COVID‐19 traumatic stress, cumulative trauma, and race to posttraumatic stress disorder symptoms

Abstract: The purpose of this study was to test if coronavirus disease 2019 (COVID‐19) traumatic stress predicts posttraumatic stress disorder (PTSD) symptoms after cumulative trauma and whether there is a three‐way interaction between COVID‐19 traumatic stress, cumulative trauma, and race in the prediction of PTSD. Using a cross‐sectional design, a diverse sample of 745 participants completed measures of cumulative trauma, COVID‐19 traumatic stress, and PTSD. COVID‐19 traumatic stress accounted for a significant amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…First, we expand the understanding of the relationships among multiple stressors and mental health outcomes. Although recently researchers have suggested that additional attention be given to the exacerbating effect of the COVID-19 pandemic on pre-existing psychopathology symptoms [ 52 ], relatively little empirical research has been conducted on this. The current study, however, demonstrates the utility of the sensitization model in the context of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…First, we expand the understanding of the relationships among multiple stressors and mental health outcomes. Although recently researchers have suggested that additional attention be given to the exacerbating effect of the COVID-19 pandemic on pre-existing psychopathology symptoms [ 52 ], relatively little empirical research has been conducted on this. The current study, however, demonstrates the utility of the sensitization model in the context of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling replicated support for the severe impact of COVID-19 on health, mental health, and cognitive functions (e.g., Kira, Alpay, Ayna et al, 2021; Liu et al, 2021; Prati & Mancini, 2021). The stressors of COVID-19 accounted for substantial unique variance in posttraumatic stress disorder (PTSD) after accounting for the variance explained by all prior cumulative stressors and traumas (Ashby et al., 2022; Kira, Shuwiekh, Ashby, Elwakeel et al, 2021). There is compelling support for the effects of CTS or Type III trauma on PTSD (e.g., Nuttman-Shwartz & Shoval-Zuckerman, 2016).…”
Section: Hypothesesmentioning
confidence: 99%
“…pandemic varies across different sociocultural contexts related to country of residence. These results provide insight into how tailored interventions are necessary based on previous traumatic events experienced, the level of locus of control individuals have, and the countries in which they reside.The next article, written byAshby et al (2022), entitled "The Relationship of Cumulative Trauma, and Race to Post Traumatic Stress Disorder Symptoms." The overall goal of this manuscript was to explore if COVID-19 traumatic stress predicted posttraumatic stress disorder (PTSD) symptoms after cumulative trauma across three domains: COVID-19, cumulative trauma, and race.…”
mentioning
confidence: 99%
“…The next article, written by Ashby et al ( 2022 ), entitled “ The Relationship of COVID‐19 Traumatic Stress, Cumulative Trauma, and Race to Post Traumatic Stress Disorder Symptoms .” The overall goal of this manuscript was to explore if COVID‐19 traumatic stress predicted posttraumatic stress disorder (PTSD) symptoms after cumulative trauma across three domains: COVID‐19, cumulative trauma, and race. The authors conducted a survey with a diverse sample who completed the cumulative stressors and traumas scale, COVID‐19 traumatic stress scale, and the posttraumatic stress disorders scale.…”
mentioning
confidence: 99%